1997
DOI: 10.1063/1.366253
|View full text |Cite
|
Sign up to set email alerts
|

Field effect-induced quasi-one-dimensional electron transport in GaAs/AlxGa1−xAsheterostructures

Abstract: We describe an approach to realize quasi-one-dimensional electron gases using an undoped GaAs/AlxGa1−xAsheterostructure. It is demonstrated that with a combination of ion implanted ohmic regions and a narrow top gate, a quasi-one-dimensional electron gas with a very high electron density can be formed. The width of the narrow top gate is varied between 0.4 and 1.0 μm. The wires are characterized by low temperature magnetotransport experiments. The effective wire width is found to be comparable to the gate widt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Apart from local depletion it has been demonstrated that a positive voltage applied to a gate electrode on top of a suitable undoped GaAs/AlGaAs heterostructure induces an electron gas. The technique has been used to prepare field-effect induced quantum wires with a minimum width of 0.4 µm and a length of 6 µm [7].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from local depletion it has been demonstrated that a positive voltage applied to a gate electrode on top of a suitable undoped GaAs/AlGaAs heterostructure induces an electron gas. The technique has been used to prepare field-effect induced quantum wires with a minimum width of 0.4 µm and a length of 6 µm [7].…”
Section: Introductionmentioning
confidence: 99%